Interannual variability in the reproductive cycle of Ruditapes philippinarum influenced by environmental and parasitic factors on the west-coast of Korea - Thatchaneshkanth, S.; Jeong-Hwa, K.; Kwang-Sik, C.; Hyun-Sung, Y. (Elsevier, 2025)
Extensive studies have shown that geographic variation, primarily driven by environmental factors, affects the reproductive cycle duration, gametogenesis, and spawning periods of the Manila clam, Ruditapes philippinarum. From February 2008 to December 2010, we monitored the annual reproductive cycle of Manila clams on a tidal flat in Garorim Bay, located on Korea’s west coast. In adult males, spermatogenesis began between December and February, reaching a peak (90 %) by March and April. Partial spawning in males occurred from May to July, coinciding with seawater temperatures rising from 11.2 to 20.0 ◦C. In females, oogenesis commenced between January and February, while spawning began in June, reaching a peak activity level of 36 %.A brief 3-month spawning period was recorded in 2009, while in other years, spawning extended for 4–5 months. The condition index (CI) of the clams ranged from 78 to 139, and fluctuations in CI during the spawning season indicated multiple spawning peaks in males, while females exhibited a single peak. The intensity of the protozoan parasite Perkinsus olseni infection ranged from 0 to 1.4x105 cells per gram of gill tissue, reflecting a low infection level compared to clams from other tidal flats on the west coast. Overall, variations in reproductive stages and CI at the study site appeared to be primarily influenced by seasonal fluctuations in water temperature and food availability, with negligible impact from parasite infection.
Keywords: Annual gametogenesis; Manila clams; Ruditapes philippinarum; Parasitic infection; Coastal ecosystems